Value of one additional injection at the root of the limb in the lymphoscintigraphic evaluation and management of primary and secondary lower-limb lymphedemas. - Pierre Bourgeois; Olivier Leduc (PLoS ONE)
Introduction The classical lymphoscintigraphic investigations of lower-limb lymphatic edema [LLLE] sometimes reveal either no or few lymph nodes [LNs] at the root of the limb[s] and/or in the abdomen. The aim of the present paper is to report the results of performing one additional injection at the root of the edematous limb[s] to force the visualization of the LNs and/or to demonstrate the collateral lymphatic pathways in such patients. Methods and findings We retrospectively reviewed our database and found 99 patients [44 primary LLLE with 47 limbs injected and 55 with LLLE secondary to treatments for cancer with 64 limbs injected] where such an additional injection had been performed. In the 43 LLLE patients where no LNs were seen at the end of the classical exam [15 primary LLLE and 28 secondary LLLE], the extra injection showed lymphatic drainage toward LN[s] in all except 3 and when at least one LN was seen, the injection showed lymphatic drainage in every case toward the same ipsilateral [inguinal and/or iliac] LNs [as shown by the classical injection] and/or toward additional LNs. In 40.7% of patients, we observed one or more additional lymphatic pathways: prepubic superficial lymphatic vessels [LV] crossing the midline anteriorly toward contralateral inguinal LNs in 21 [18.9%], "posterior" LV [toward contralateral inguinal LNs and/or ipsi- or contralateral lumbo-aortic and/or para-renal LNs] in 14 [12.6%], but deep LV toward the ipsilateral common iliac LNs passing between the gluteal muscles in 32 [28.8%]. Conclusion Our work pinpoints one limitation of classical bipedal radionuclide lymphangiography. In patients with primary and secondary LLLE where inguinal and/or iliac LNs cannot be seen on bipedal radionuclide lymphangiography, this additional injection reveals the true lympho-nodal status and shows unexpected collateral lymphatic pathways in 40% of cases. Such information is of the utmost importance in LLLE management and its acquisition is consequently recommended in these patients.